2021
DOI: 10.1136/bmjopen-2020-044684
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for severity of COVID-19: a rapid review to inform vaccine prioritisation in Canada

Abstract: ObjectivesRapid review to determine the magnitude of association between potential risk factors and severity of COVID-19, to inform vaccine prioritisation in Canada.SettingOvid MEDLINE(R) ALL, Epistemonikos COVID-19 in L·OVE Platform, McMaster COVID-19 Evidence Alerts and websites were searched to 15 June 2020. Eligible studies were conducted in high-income countries and used multivariate analyses.ParticipantsAfter piloting, screening, data extraction and quality appraisal were performed by a single experience… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 54 publications
(61 reference statements)
4
49
1
1
Order By: Relevance
“…This finding is reassuring, given that these groups can have impaired immune responses to other vaccines 28-30 and are most at risk for severe and prolonged manifestations of Covid-19 and death. 8 , 9 , 13 , 14 Second, in Black adults and Hispanic adults, who have been disproportionately affected by Covid-19, mRNA-based vaccines were similarly effective with respect to Covid-19–associated hospitalization and an emergency department or urgent care clinic visit. 9-11 , 14 , 31 Third, the effectiveness of full mRNA-based vaccination remained consistently high at least until 112 days after the second dose, which was the longest interval since vaccination during our study period.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This finding is reassuring, given that these groups can have impaired immune responses to other vaccines 28-30 and are most at risk for severe and prolonged manifestations of Covid-19 and death. 8 , 9 , 13 , 14 Second, in Black adults and Hispanic adults, who have been disproportionately affected by Covid-19, mRNA-based vaccines were similarly effective with respect to Covid-19–associated hospitalization and an emergency department or urgent care clinic visit. 9-11 , 14 , 31 Third, the effectiveness of full mRNA-based vaccination remained consistently high at least until 112 days after the second dose, which was the longest interval since vaccination during our study period.…”
Section: Discussionmentioning
confidence: 96%
“… 8 , 9 , 13 , 14 Second, in Black adults and Hispanic adults, who have been disproportionately affected by Covid-19, mRNA-based vaccines were similarly effective with respect to Covid-19–associated hospitalization and an emergency department or urgent care clinic visit. 9-11 , 14 , 31 Third, the effectiveness of full mRNA-based vaccination remained consistently high at least until 112 days after the second dose, which was the longest interval since vaccination during our study period. Fourth, we examined the effectiveness of all three authorized Covid-19 vaccines in the United States.…”
Section: Discussionmentioning
confidence: 96%
“…Another large-scale British primary care study of more than 17 million individuals revealed similar risk factors as above [60]. There is also a relatively large literature on the study of risk factors associated with severe or fatal disease [15][16][17][18][61][62][63][64]. Some commonly reported risk factors included age, sex, obesity, T2DM, HT, renal, cardiometabolic, and respiratory disorders.…”
Section: Previous Relevant Workmentioning
confidence: 93%
“…While predictive performance is the main concern in most previous studies, we argue that ML models can also provide important insights into individual contributing factors and the pattern of complex relationships between risk factors and the outcome. While many have studied risk factors of COVID-19 susceptibility or severity in the UKBB [12][13][14] or other cohorts (eg, [8,[15][16][17][18]), most relied on conventional linear models. As such, nonlinear effects and interactions between variables may be missed.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this risk of severe and even fatal COVID-19, governments and relevant public health authorities worldwide enforced nationwide lockdown/quarantine measures, aiming to decrease the transmission of SARS-CoV-2 among the general population, and hence protect the health of vulnerable individuals [4][5][6][7]. Based on robust clinical and epidemiological evidence, it is now clear that, in addition to older age and male sex, susceptibility to severe COVID-19 is directly associated with a number of chronic cardio-metabolic diseases, such as obesity, diabetes, hypertension and metabolic syndrome [8][9][10][11][12][13][14]. Of note, with the exception of advanced age and male sex, the same cardio-metabolic risk factors which predispose to severe COVID-19 are also highly prevalent among women with polycystic ovary syndrome (PCOS) [15,16], placing this female patient population at potentially increased risk during the COVID-19 pandemic [17].…”
Section: Introductionmentioning
confidence: 99%